Weekday bicycle traffic and crash rates during the COVID-19 pandemic. (December 2021) - Monfort, Samuel S.; Cicchino, Jessica B.; Patton, David
Abstract: Introduction: One of the most consequential effects of the COVID-19 lockdowns was a dramatic reduction in travel during peak hours. Transportation modes also shifted—in particular, travel by car became more rare while bicycling saw a resurgence. Given that a typical year sees the most severe bicycle crashes in peak commuter traffic, the shift toward bicycle travel that occurred in 2020 will likely have been accompanied by unique changes in rider behavior (e.g., where and when they choose to ride) as well as the frequency and severity of vehicle-bicycle crashes. Methods: The current study compared weekday bicycle traffic and crashes in Arlington, VA from March–December 2020 with the same period from years prior, 2013–2019. Bicycle traffic data were obtained from 16 embedded counters placed throughout the study area, in both off-road trails and on-road bike lanes. Results: We found that 2020 midday traffic nearly doubled compared to the year before, increasing from an average of 68 riders per hour to 120 (+76%). By contrast, morning traffic fell from an average of 87 riders per hour to just 45 (−49%). Change in evening traffic depended on the location of the counters: more evening bicycles were counted on off-road, multi-use trails (+6%) but fewer on on-road lanes (−27%). The changes to 2020 bicycle traffic patterns were also associated with a 28% reduction in bicycle injury crash rate per counted cyclist. Conclusion: The reduced crash risk observed in 2020 was likely due in part to the reduction of morning, on-road bicycle travel, which past research has found to be particularly dangerous for riders. Conversely, the availability of multi-use off-road trails seems to have been a protective factor against bicycle-motor vehicle crash risk in the face of greater bicycle travel volume. Highlights: We compared bicycle traffic and crash data during the 2020 Coronavirus-19 pandemic to traffic and crashes from prior years. Midday bicycle traffic in 2020 nearly doubled compared to the year before (+76%) and morning traffic fell by half (−49%). More evening bicycles were counted on off-road, multi-use trails (+6%) but fewer were counted on on-road lanes (−27%). The changes to 2020 bicycle traffic were associated with a 28% reduction in bicycle injury crash rate per counted cyclist. Our findings point to the importance of off-road trails in absorbing changes in travel patterns without raising injury crash risk.